IMPLIKASI BAHASA HUKUM DALAM LARANGAN PERKAWINAN TERHADAP UNDANG-UNDANG NO. 1 TAHUN 1974 TERHADAP MASYARAKAT - rohadi hadi (Jurnal De Jure Muhammadiyah Cirebon, 2017)
The legal language implications of the marriage ban set forth in Act no. 1 of 1974 against the society, ie some people consider that the words contained in the provisions are too long-winded so that this confuses the community therefore the need for the use of legal language is easy to understand, firm, straightforward and not cause interpretation that resulted in his fault understanding in interpreting the provisions contained in Act no. 1 of 1974 in connection with the ban on marriage. Keywords: Legal Language, Marriage Ban, Act no. 1 of 1974